2019
DOI: 10.3389/fimmu.2019.00580
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells in Cardiac Fibrosis: New Insights Suggest Opportunities for Intervention

Abstract: Mast cells (MC) are innate immune cells present in virtually all body tissues with key roles in allergic disease and host defense. MCs recognize damage-associated molecular patterns (DAMPs) through expression of multiple receptors including Toll-like receptors and the IL-33 receptor ST2. MCs can be activated to degranulate and release pre-formed mediators, to synthesize and secrete cytokines and chemokines without degranulation, and/or to produce lipid mediators. MC numbers are generally increased at sites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 125 publications
(142 reference statements)
0
64
0
1
Order By: Relevance
“…To date, a plethora of compelling results suggest roles for MCs in cardiac fibrosis (Legere et al, 2019). For one, in injury, the presence of DAMPs can trigger MC degranulation, which results in the release of inflammatory mediators like tryptase, chymase, IL-1β, and TNFα (Legere et al, 2019).…”
Section: Mast Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, a plethora of compelling results suggest roles for MCs in cardiac fibrosis (Legere et al, 2019). For one, in injury, the presence of DAMPs can trigger MC degranulation, which results in the release of inflammatory mediators like tryptase, chymase, IL-1β, and TNFα (Legere et al, 2019).…”
Section: Mast Cellsmentioning
confidence: 99%
“…To date, a plethora of compelling results suggest roles for MCs in cardiac fibrosis (Legere et al, 2019). For one, in injury, the presence of DAMPs can trigger MC degranulation, which results in the release of inflammatory mediators like tryptase, chymase, IL-1β, and TNFα (Legere et al, 2019). Studies have shown that both tryptase and chymase activate TGFβ, a potent fibrogenic mediator known to promote myofibroblast differentiation and collagen production (Lindstedt et al, 2001;Tatler et al, 2008;Legere et al, 2019).…”
Section: Mast Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that baseline tryptase is positively correlated with the degree of coronary artery disease suggests either a role for MCs in the pathogenesis of coronary artery disease or activation as a bystander process [57]. MCs found in cardiac tissue are increasingly being recognized in the pathophysiology of various cardiac disorders [58].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…From a general tissue disease perspective, several studies have similarly emphasized their detrimental role to tissue remodeling outcomes [12][13][14] . However, research has also produced confounding results [15][16][17][18] or evidence of their beneficial contributions to select cases of native tissue repair or inflammatory resolution 16,19,20 , suggesting a greater functional complexity and potential to be utilized in therapeutic design. Based on recent evidence suggesting that mast cells can have beneficially influences on native tissue remodeling outcomes, we explored the role mast cells play in regulation of biomaterial scaffold-induced immunomodulatory responses, demonstrating its critical regulatory contribution to the pro-inflammatory to anti-inflammatory/pro-remodeling transition that deviates in a gender specific manner.…”
mentioning
confidence: 99%